Introducing a property right over data in the EU: the data producer's right – an evaluation. Issue 1 (2nd January 2020) - Stepanov, Ivan
ABSTRACT: The article discusses the nature and justification for the introduction of the data producer's right. The European Commission in its efforts to boost the European data economy is contemplating the introduction of an IPR over data. Firstly, the article surveys whether the current EU legal framework grants property rights over data and how the established IPRs like copyright or database protection treat data as the object of property. Secondly, drawing upon property theory the article determines whether the data producer's right can be regarded as a property right at all. Thirdly, the data producer's right is assessed in light of some legal and economic justifications for the introduction of property rights. Considering that the Commission proposed the introduction of the right on the grounds of economic policy, the analysis will endeavor to shed some light on whether the current proposal might achieve the stated goals.